Techies Enterprise: Pineapple Peeler / Mohamad Farhan Salehon [et al.] - Salehon, Mohamad Farhan; Che' HarUn, Mohamad Faiz; Daud, Mohd Fazreel; Shamsul Bahar, Muhammad Syahid; Hishamuddin, Zuhairi (2016)
Techies Enterprise is a new company that fully-operated in Malaysia. The name of the company is come out from the imagination by the General Manager, Mohamad Farhan Bin Salehon, and has been agreed by the partnerships members.